Serious adverse drug events associated with psychotropic treatment of bipolar or schizoaffective disorder: a 17-year follow-up on the LiSIE retrospective cohort study - Truedson, Petra; Ott, Michael; Wahlström, Lisa; Lundqvist, Robert; Maripuu, Martin; Lindmark, Krister; Lieber, Ingrid; Werneke, Ursula (Frontiers in Psychiatry, 2024)
Introduction Mood stabilisers and other psychotropic drugs can lead to serious adverse drug events (ADEs). However, the incidence remains unknown. We aimed to (a) determine the incidence of serious ADEs in patients with bipolar or schizoaffective disorders, (b) explore the role of lithium exposure, and (c) describe the aetiology. Methods This study is part of the LiSIE (Lithium—Study into Effects and Side Effects) retrospective cohort study. Between 2001 and 2017, patients in the Swedish region of Norrbotten, with a diagnosis of bipolar or schizoaffective disorder, were screened for serious ADEs to psychotropic drugs, having resulted in critical, post-anaesthesia, or intensive care. We determined the incidence rate of serious ADEs/1,000 person-years (PY). Results In 1,521 patients, we identified 41 serious ADEs, yielding an incidence rate of 1.9 events per 1,000 PY. The incidence rate ratio (IRR) between ADEs with lithium present and causally implicated and ADEs without lithium exposure was significant at 2.59 (95% CI 1.20–5.51; p = 0.0094). The IRR of ADEs in patients <65 and ≥65 years was significant at 3.36 (95% CI 1.63–6.63; p = 0.0007). The most common ADEs were chronic lithium intoxication, oversedation, and cardiac/blood pressure-related events. Discussion Serious ADEs related to treatment of bipolar (BD) or schizoaffective disorder (SZD) were uncommon but not rare. Older individuals were particularly at risk. The risk was higher in individuals exposed to lithium. Serum lithium concentration should always be checked when patients present with new or unclear somatic symptoms. However, severe ADEs also occurred with other mood stabilisers and other psychotropic drugs.